2006
DOI: 10.1152/ajpendo.00638.2005
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition does not alter the activation of β-cell neogenesis and replication in adult rats after partial pancreatectomy

Abstract: In previous work, we demonstrated that a 65% protein calorie food restriction started during the third trimester of gestation in rats caused a reduced ␤-cell mass at 4 days of life that persisted until adult age. In this study with adult undernourished (U) rats, we investigated 1) whether undernutrition affects the ␤-cell growth potential and both ␤-cell proliferation and differentiation and 2) the implication of the IGFs, highly responsive to nutritional status, in these processes. To this end, we used the 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 64 publications
(69 reference statements)
2
12
0
1
Order By: Relevance
“…So, although new islets can form by neogenesis in the undernourished animals it appears that they cannot get larger as reflected by the high number of very small islets in restricted pups at the end of the suckling period. This agrees with previous results obtained by our group after partial pancreatectomy of undernourished adult rats (Fernández et al 2006) and with those observed in diabetic models induced by selective perfusion of alloxan (Waguri et al 1997) or by the administration of low dose of streptozotocin (Bernard et al 1999). In contrast, studies performed in rats submitted to a low-protein diet reported impaired islet cell proliferation and increased islet cell apoptosis (Petrik et al 1999, Dumortier et al 2007) but b-cell neogenesis when submitted to a low-energy diet (Garofano et al 2000, Dumortier et al 2007.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…So, although new islets can form by neogenesis in the undernourished animals it appears that they cannot get larger as reflected by the high number of very small islets in restricted pups at the end of the suckling period. This agrees with previous results obtained by our group after partial pancreatectomy of undernourished adult rats (Fernández et al 2006) and with those observed in diabetic models induced by selective perfusion of alloxan (Waguri et al 1997) or by the administration of low dose of streptozotocin (Bernard et al 1999). In contrast, studies performed in rats submitted to a low-protein diet reported impaired islet cell proliferation and increased islet cell apoptosis (Petrik et al 1999, Dumortier et al 2007) but b-cell neogenesis when submitted to a low-energy diet (Garofano et al 2000, Dumortier et al 2007.…”
Section: Discussionsupporting
confidence: 92%
“…Immunohistochemistry was performed as previously described (Fernández et al 2006). Pancreas sections (5 mm) at fixed intervals throughout the paraffin block were immunostained for insulin using guinea pig anti-porcine insulin (ICN, Biolink, Barcelona, Spain) and a peroxidase-conjugated rabbit anti-guinea pig IgG (Dako Diagnostics, Barcelona, Spain).…”
Section: Immunohistochemistry and Morphometrymentioning
confidence: 99%
See 1 more Smart Citation
“…In 9-month-old undernourished rats, insulinemia has been normalized, which could be explained by a regenerative capacity of ␤-cells previously reported in undernourished adult rats (50). After rehabilitation, these rats became hypoinsulinemic, regardless of dietary regime.…”
Section: Discussionsupporting
confidence: 54%
“…Meskipun demikian, dengan tujuan penelitian tertentu beberapa peneliti sampai sekarang masih menggunakan metode tersebut (Fernandez et al, 2006;Ani et al, 2006).…”
Section: Hewan Percobaan Hiperglikemiaunclassified